Risk Orientation and SME Performance: The Mediating Role of Management Accounting - Ahmad, Kamilah; Ruslan, Rumaizah; Zabri, Shafie Mohamed; Hussin, Mohd Khairul Adne Mat (International Journal of Economics and Financial Issues, 2025)
Limited studies have examined how risk orientation affects the adoption of management accounting (MA) and performance in small and medium-sized enterprises (SMEs). Performance in SMEs is influenced by various factors, including the ability to adapt to changes in the market and the effective use of resources. Understanding how risk orientation impacts the adoption of management accounting practices can offer helpful tips for enhancing overall business performance and sustainability in this sector. This study seeks to examine the effects of risk orientation and MA on performance using structural equation modelling. A quantitative study was established where a questionnaire survey was administered to Malaysian SMEs across different sectors. Based on 189 valid responses, the results indicate that MAs partially mediate the relationship between risk orientation and SMEs’ performance. The findings provide significant information for identifying the underlying factors within the setting of small businesses in improving financial resilience of SMEs. Our findings offer practitioners valuable insight about how risk orientation and management accounting can consequently affect the positive outcomes of organisational performance.